Design and Implementation of Robust Digital Watermarking using Hybrid technique for Copyright Protection Digital data (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research paper, we concerned with the creation of a comprehensive digital watermarking framework based on DWT. In order to improve imperceptibility and robustness, the watermark is inserted only in chosen frames. The picked frames are the frames in which a change of scene happens. The key objective, therefore, is to detect the correct transformation of the scene. The Scene Shift Detector identifies correct frames that have been modified using the successive histogram discrepancy process. Two schemes proposed using the same method of scene detection. Both suggested schemes achieve a good watermark rating with good (PSNR) valuesThere, Because the watermark integration is done exclusively on the scene with low and high frequency DWT subbands, the image processing assaults, geometric aggressions, JPEG compression, high normalised image attacks are immune,and low-bit error rates (BER). Comparative analysis of two algorithms is also carried out.